Youth and parent preferences for an ideal AP system: It is all about reducing burden. Issue 7 (9th August 2021) - Commissariat, Persis V.; Roethke, Lindsay C.; Finnegan, Jennifer L.; Guo, Zijing; Volkening, Lisa K.; Butler, Deborah A.; Dassau, Eyal; Weinzimer, Stuart A.; Laffel, Lori M.
Abstract: Background: As new diabetes technologies improve to better manage glucose levels, users' priorities for future technologies may shift to prioritize burden reduction and ease of use. We used qualitative methods to explore youth and parent desired features of an "ideal" artificial pancreas (AP) system. Methods: We conducted semi‐structured interviews with 39 youth, ages 10–25 years, and 44 parents. Interviews were audio‐recorded, transcribed, and coded using thematic analysis. Results: Youth (79% female, 82% non‐Hispanic white) were (M ± SD) ages 17.0 ± 4.7 years, with diabetes for 9.4 ± 4.9 years, and HbA1c of 8.4 ± 1.1%; 79% were pump‐treated and 82% used CGM. Of parents, 91% were mothers and 86% were non‐Hispanic white. Participants suggested various ways in which an ideal AP system could reduce physical and emotional burdens of diabetes. Physical burdens could be reduced by lessening user responsibilities to manage glucose for food and exercise, and wear or carry devices. Emotional burden could be reduced by mitigating negative emotional reactions to sound and frequency of alerts, while increasing feelings of normalcy. Youth and parents differed in their suggestions to reduce emotional burden. Participants suggested features that would improve glycemia, but nearly always in the context of how the feature would directly reduce their diabetes‐specific burden. Conclusions: Although participants expressed interest in improving glucose levels, the pervasive desire among suggested features of an ideal AP system was to minimize the burden of diabetes. Understanding and addressing users' priorities to reduce physical and emotional burden will be necessary to enhance uptake and maintain use of future AP systems.